Overview Motivasi Belajar Pendidikan Agama Islam: Analisis Menggunakan Bibliometrik - Nofmiyati Nofmiyati; Miftahuddin Miftahuddin; Darmawati Darmawati (Madania: Jurnal Ilmu-Ilmu Keislaman, 2023)
Motivation is closely related to the individual's self; positive motivation will give birth to positive things, as well as vice versa. Learning motivation can change one's mindset, success, and interest. Whereas in Islamic religious education, learning motivation is more closely related to religion. The purpose of this study was to look at the motivation for learning Islamic education using bibliometric analysis of years, keywords, and countries. While the method used was searching for data from Scopus with the keywords "motivation to learn" OR "Islamic religious education," it obtained 878 documents after being limited, then entered the Openrefine and Vosviewer stages by storing literature on Mendeley. Research results show that the most documented year is 2022 with 246 documents, while the most commonly used keyword is motivation and the most heavily criticized state has 143 documents.